The Influence of Product Quality and Price on Consumer Purchase Interest in Souvenir Products in the Baduy Cultural Tourism Area - Ajid; Nia Sonani; Mulyana Gustira Putra (ARTOKULO : Journal of Accounting, Economic and Management, 2024)
The purpose of this study was to find out empirically about the role of the influence of product quality and price on consumer buying interest in souvenir products in the Baduy cultural tourism area. This research was conducted in Ciboleger, the Outer Baduy Tribe Tourism Area. The samples were selected using a purposive method and 240 respondents were sampled. The method used in this study is a quantitative method using multiple linear regression analysis with the help of SPSS version 22. The population in this study is consumers of souvenir products in the cultural tourism area of the Baduy tribe, totaling 770 people. The sample using the Isaac and Micheal formula obtained the number of respondents as many as 240 people. In this study the instrument used to manage primary data was a questionnaire measured by a Likert scale used to measure attitudes, opinions, and perceptions of a person or group of people about social phenomena. From the results of the F test, the significance value of the ANOVA test is 000 <0.05. Therefore, H0 is rejected and H1 is accepted, which means that there is a significant influence between the variables Product Quality and Price which together affect variable Y, meaning that Product Quality and Price become one unit in Souvenir Products in the Baduy Cultural Tourism Area so that the implementation these two variables can increase